Ligand-independent activation of the platelet-derived growth factor beta receptor: requirements for bovine papillomavirus E5-induced mitogenic signaling. - Drummond-Barbosa, D A (1995)
The E5 protein of bovine papillomavirus type 1 binds to and activates the endogenous platelet-derived growth factor (PDGF) beta receptor in fibroblasts, resulting in cell transformation. We have developed a functional assay to test the ability of PDGF beta receptor mutants to mediate a mitogenic signal initiated by the E5 protein. Lymphoid Ba/F3 cells are strictly dependent on interleukin-3 for growth, but coexpression of the wild-type PDGF beta receptor and the E5 or v-sis-encoded protein generated a mitogenic signal which allowed Ba/F3-derived cells to proliferate in the absence of interleukin-3. In these cells, the E5 protein bound to and caused increased tyrosine phosphorylation of both the mature and the precursor forms of the wild-type PDGF beta receptor. The tyrosine kinase activity of the receptor was necessary for E5-induced receptor tyrosine phosphorylation and mitogenic activity but not for complex formation with the E5 protein. In contrast, the PDGF-binding domain of the receptor was not required for complex formation with the E5 protein, E5-induced tyrosine phosphorylation or mitogenic activity, demonstrating that E5-mediated receptor activation is ligand independent. Analysis of receptor mutants lacking various combinations of tyrosine phosphorylation sites revealed that the E5 and v-sis-encoded proteins display similar requirements for signaling and suggested that the wild-type PDGF beta receptor can generate multiple independent mitogenic signals. Importantly, these mutants dissociated two activities of the PDGF beta receptor tyrosine kinase, both of which are required for sustained mitogenic signaling: (i) receptor autophosphorylation and creation of binding sites for SH2 domain-containing proteins and (ii) phosphorylation of substrates other than the receptor itself.